A treatise of human nature - Hume, David (Clarendon Press ; Oxford University Press, 1978)
The growth of pension funds has been nothing short of astronomical. Pension funds now dominate the world's financial markets, affecting nations' wealth, community development, and industrial well being. Yet little is known about their structure and organization. Pension funds and their agents in the investment industry control enormous sums of money, profoundly affecting the structure and performance of nation-states and the global economy. At the same time, it is also apparent that many western governments are retreating from the provision of 'public good' once thought essential to the fabric of urban life. Clark agues that if we are to understand the long-term future of the western economies (in general) and our communities (in particular), we need also to understand how institutional investors allocate assets, mobilize funds, and make investment decisions. There are few studies of the relationship between pension funds and the financial services industry. Pension Fund Capitalism fills an important gap in the literature as well as the intersection between pension funds and public policy.